PENGARUH LASER ACUPOINT TERHADAP ANSIETAS PADA LANSIA - Melani Kartika Sari; Maulana Rahmat Hidayatullah (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: Anxiety is a psychological problem that often occurs in the elderly. Anxiety is a feeling of worry whose object is biased or unclear towards something that is not certain. This is often related to the various physical, social, and economic changes that occur in the elderly due to the aging process. Laser acupoint is an alternative intervention developed from acupuncture and acupressure using low-energy laser light which aims to balance body energy and homeostasis. Purpose: The aims of this study was to analyze the effect of laser acupoint on anxiety in the elderly. Methods: This type of research is pre-experimental, one group pre-post test design with a total sample of 26 respondents. Data were collected using the Geriatric Anxiety Inventory (GAI). The points used on the Laser Acupoint are He Ku (Li. 4), Sen Men (HT.7), Tai Chong (LR.3) and Sing Cien (LR. 2). The intervention was carried out for 20 minutes, with a frequency of 2 times a week, and carried out for 6 times of therapy. Data analysis used the Wilcoxon sign rank test. Result: the result of p = 0.00 with a confidence level of 95%. This shows the effect of laser acupoint on anxiety in the elderly. Conclusion: Acupoint laser can be used as an alternative intervention in overcoming anxiety in the elderly.Keywords: Laser acupoint; Anxiety; Elderly